A Critical Analysis of Implications of Inclusive Education Provisions for Initial Teacher Education (ITE) Programme Content and Its Possible Effects on Inclusive Primary School Teaching in the Context of Aotearoa New Zealand - Gajdocsi, Erika (Auckland University of Technology, 2023)
This research study is centred around the ways inclusive education policies frame inclusive education content within initial teacher education (ITE) programmes for inclusive primary teaching practices in Aotearoa New Zealand. The study also examines the extent to which policy is evident beyond itself as a document in the community. The concept of inclusive education is preceded by special needs education, a concept that focuses on individual students and their deficits rather than recognising all learners as part of the same learning community. The development of inclusive education as a concept has its roots in human rights movements and legislative changes worldwide. These movements and international policies influence the New Zealand inclusive education policy environment. Aotearoa New Zealand has been responsive to the implementation of inclusive education at policy level; however, discrepancies are found between policy intention and policy implementation. The study was framed by social constructionism and structuration theory as conceptual frameworks. The conceptual frameworks enabled the examination of structure-agency relationship between policy, ITE providers, and teaching practices in Aotearoa New Zealand. The study used critical content analysis as a method for the policy analysis and found that both the special needs education and inclusive education concepts are still circulating in policy documents today, often interchangeably. The critical content analysis revealed that language use affects the extent inclusion is evident in ITE programme content and teaching practices in Aotearoa New Zealand. The often interchangeable nature of referring to inclusive education as special needs education creates confusion and contributes to policy intention not aligning with policy implementation at ITE provider and school levels. Policies released by the New Zealand government were found to align more with the historical special needs education initiatives, whereas Teaching Council Aotearoa New Zealand policies and their ITE programme development guidelines were more in-line with international concepts of inclusive education in terms of language use. Both concepts were evident, often interchangeably, in paper descriptors and in evidence of inclusive education policy beyond the documents, such as in an Education Review Office (ERO) report and news media. As special needs education terminology is still evident in policy documents, the concept of inclusive education has not been fully achieved. The term special needs education is used as a replacement for the word and concept of inclusion and inclusive education despite the difference in meaning between the two terms.